A Review on Samangadi Taila and its Effect on Wound Healing (AYUSHDHARA, 2023)
Today’s era is the era of scientific validation. So, it’s much more important to prove the thinks which we do either theoretically or practically. As we all know Vrana Chikitsa is being the matter of concern since time immemorial for all the system of medical science. If we unfold the pages of Ancient Ayurvedic literature then we will find a number of miraculous drugs or combined preparations which have magnificent effect of the treatment of Vrana. But the cause behind the back step is the unavailability of such drugs. By combining some of those drugs as per the reference of Acharya Shusruta, which are available now, we have taken a Taila preparation named as per the first ingredient in it as Samangadi Taila. Ingredients, properties, and its effect on the management of Vrana through different mode of actions as per Ayurveda are described here individually and combinedly as one preparation.In this review we are discuss on individual drug properties concerning of Vrana Chikitsa, Formulation of drugs as per classical text and explain of probable mode of action of Samangadi Taila, in addition to mentioned of source of drugs and analytical study of combined preparation under completion of formulation.